Web framework points: an effort estimation methodology for Web application development using a content management framework. Issue 9 (10th April 2015) - Barabino, Giulio; Concas, Giulio; Corona, Erika; Grechi, Daniele; Marchesi, Michele; Tigano, Danilo
Abstract: Web applications are among the most popular and relevant kinds of application. Most Web applications are developed using a content management framework (CMF). CMF helps to accelerate the publication of large amounts of information and the development of Web applications. However, developing Web applications through CMF is not exempt from cost and time overruns, as in traditional software projects. Currently, there is no estimation model able to adequately measure the effort of developing a Web application. This work presents a new methodology, called web framework points, to estimate the effort of Web applications developed with CMF. Web framework points is a hybrid methodology, composed of a sizing phase, which follows specific guidelines, and an effort estimation phase, obtained by applying a cost model to the size model of the project to estimate. The sizing of the project takes into account not only usual functional requirements, as in function points analysis, but also elements specific for developing a Web application through CMF. We also present the experimental validation of the proposed methodology, performed on a dataset of 29 real‐world projects, of which 83% show an estimation error of less than 25%. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This work presents the Web Framework Points (WFP) methodology to estimate the effort of Web applications developed with a content management framework. WFP is composed of a sizing phase, and an effort estimation phase, obtained by applying a cost model to the size model of the project to estimate. The sizing of the project takes into account not only usual functional requirements, but also elements specific for developing a Web application. We present the experimental validation of the proposed methodology.